Cerro Pelón, lágrimas de barro and the Mitch as metamorphosis of being - Alvarado Vega, Óscar Gerardo (2019)
The approach of these two stories aims to stablish an approach to what reading represents about nature as (quasi) character that accompanies the evolution of men and women who wander through it, and complement or distance, but without lose sight of the fact that nature responds to a great extent, to their occurrence, their experiences, their psychology, and their actions with others. From this perspective, the characters cease to be the center of the universe, and become part of the wild nature, usually, but passive at other times (the least).